prove that LHS=RHS without evaluating the determinant l a1+b1t a2+b2t a3+b3t l= l a1 a2 a3 l l a1t+b1 a2t+b2 a3t+b3 l= (1-t^2) l b1 b2 b3 l l c1 c2 c3 l= l c1 c2 c3 l
Follow Math Help Forum on Facebook and Google+
Originally Posted by alexandrabel90 prove that LHS=RHS without evaluating the determinant l a1+b1t a2+b2t a3+b3t l= l a1 a2 a3 l l a1t+b1 a2t+b2 a3t+b3 l= (1-t^2) l b1 b2 b3 l l c1 c2 c3 l= l c1 c2 c3 l This is nearly impossible to read. Are you trying to prove that this is true?
yes(:
View Tag Cloud